PERAN MEREK TERHADAP PRODUK: SEBUAH PERSPEKTIF YURIDIS BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Subagio, Hani (Jurnal Ilmu Administrasi dan Bisnis, 2020)
The aim of this study is to determine the application of trademark law in Indonesia based on Law Number 20 of 2016 concerning trademarks and geographical indications. As a form of intellectual work, brands play an important role in the world of trade in goods and services as well as global economic development. Brand also serves as a differentiator between products from one manufacturer to another. The significance of a brand makes the brand commercially valuable wealth. The importance of a brand is often used as a salable commodity for trading, resulting in the practice of counterfeiting and imitation based on bad faith which ultimately results in losses to the original company.